Count on Us - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses fundamental issues in global development and the World Bank Group's role in helping countries and the private sector meet the greatest challenges in development. He speaks about the twin goals, to end extreme poverty by 2030 and to boost shared prosperity. Due to television, everyone knows how everyone else lives. We must not remain voluntarily blind to the impact of economic choices on the poor and vulnerable. He added that we must ensure that our economic progress does not irreparably compromise our children’s future due to climate change. World Bank’s lending capacity – or the amount of loans we can carry on our balance sheet -- will increase by $100 billion dollars in the next decade, to roughly $300 billion dollars. He concludes by saying that all parts of our global society must unite to translate the vision of a more just, sustainable economy into the resolute action. That will be our legacy to the future. Dr. Kim fielded questions.